2014
DOI: 10.1094/phyto-11-13-0314-r
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Molecular Analyses Support Asexual Reproduction of Puccinia striiformis f. sp. tritici in the U.S. Pacific Northwest

Abstract: Wheat stripe rust, caused by Puccinia striiformis f. sp. tritici, occurs every year and causes significant yield losses in the U.S. Pacific Northwest (PNW). A large number of P. striiformis f. tritici races are identified every year and predominant races have changed rapidly. Barberry and mahonia plants, which have been identified under controlled conditions as alternate hosts for the fungus, are found in the region. However, whether sexual reproduction occurs in the P. striiformis f. sp. tritici population un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…In the present study, high telia production may be explained by two hypotheses: one is the possibility of sexuality in the Pst population in some parts of Canada, which is possible because common barberry exists in the province of Ontario (Tom Fetch, personal communication) and it might exist in the province of British Columbia, which is close to the PNW of the USA, where barberry is reported (Cheng and Chen, ). In Canada, the existence of common barberry (an alternate host for the oat stem rust fungus) has resulted in oat stem rust races that form telia faster and produce more telia as compared to clonal races (T. Fetch, pers.…”
Section: Discussionmentioning
confidence: 72%
“…In the present study, high telia production may be explained by two hypotheses: one is the possibility of sexuality in the Pst population in some parts of Canada, which is possible because common barberry exists in the province of Ontario (Tom Fetch, personal communication) and it might exist in the province of British Columbia, which is close to the PNW of the USA, where barberry is reported (Cheng and Chen, ). In Canada, the existence of common barberry (an alternate host for the oat stem rust fungus) has resulted in oat stem rust races that form telia faster and produce more telia as compared to clonal races (T. Fetch, pers.…”
Section: Discussionmentioning
confidence: 72%
“…This can be explained by the property of Pst and EMS mutagenesis. i) The two nuclei in Pst urediniospores were found to be highly heterozygous in many isolates [37,39,58,59]. ii) Previous studies observed Pst isolates with a low virulence spectrum tended to be highly heterozygous [39,60].…”
Section: Discussionmentioning
confidence: 92%
“…Chen, unpublished data). In the United States, the Pst population reproduces asexually (34,132). A segregating population has been developed on barberry from selfing PST-127, a predominant race since 2007.…”
Section: Determination Of Homozygous and Heterozygous Virulencesmentioning
confidence: 99%